Genomic insights on DNase production in Streptococcus agalactiae ST17 and ST19 strains - Silvestre, Inês (2022)
Streptococcus agalactiae evasion from the human defense mechanisms has been linked to the production of DNases. These were proposed to contribute to the hypervirulence of S. agalactiae ST17/capsular-type III strains, mostly associated with neonatal meningitis. We performed a comparative genomic analysis between ST17 and ST19 human strains with different cell tropism and distinct DNase production phenotypes. All S. agalactiae ST17 strains, with the exception of 2211-04, were found to display DNase activity, while the opposite scenario was observed for ST19, where 1203-05 was the only DNase(+) strain. The analysis of the genetic variability of the seven genes putatively encoding secreted DNases in S. agalactiae revealed an exclusive amino acid change in the predicted signal peptide of GBS0661 (NucA) of the ST17 DNase(-), and an exclusive amino acid change alteration in GBS0609 of the ST19 DNase(+) strain. Further core-genome analysis identified some specificities (SNVs or indels) differentiating the DNase(-) ST17 2211-04 and the DNase(+) ST19 1203-05 from the remaining strains of each ST. The pan-genomic analysis evidenced an intact phage without homology in S. agalactiae and a transposon homologous to TnGBS2.3 in ST17 DNase(-) 2211-04; the transposon was also found in one ST17 DNase(+) strain, yet with a different site of insertion. A group of nine accessory genes were identified among all ST17 DNase(+) strains, including the Eco47II family restriction endonuclease and the C-5 cytosine-specific DNA methylase. None of these loci was found in any DNase(-) strain, which may suggest that these proteins might contribute to the lack of DNase activity. In summary, we provide novel insights on the genetic diversity between DNase(+) and DNase(-) strains, and identified genetic traits, namely specific mutations affecting predicted DNases (NucA and GBS0609) and differences in the accessory genome, that need further investigation as they may justify distinct DNase-related virulence phenotypes in S. agalactiae.